The role of the basic education system in promoting entrepreneurship skills - Mlambo, Gloria Buyisile; Mdhlalose, Dickson (STAI Miftahul Ula Nganjuk, 2023)
Basic education is for all in South Africa. The dawn of the democratic government in 1994 brought forth numerous curriculum changes throughout the basic education system to redress past differences. The changes saw the introduction of a subject like Technology designed to stimulate innovativeness and develop learners' creative and critical thinking skills. This study aimed to explore the role of the basic education system in promoting entrepreneurship skills, including teacher selection and evaluation, learning tools, classroom situations and support systems for the effectiveness of the system in producing learners with entrepreneurial skills. The constructivist worldview underpinned this qualitative study, using four schools within the Malelane Circuit in Mpumalanga Province. A case study explored the system's role in promoting entrepreneurship skills to learners. Senior phase technology teachers were selected for data collection, two grade 7 Technology teachers, four grade 8 Technology teachers, and four grade 9 Technology teachers. Primary data were collected through in-depth semi-structured interviews. Meanwhile, journals, books and policy documents were used for secondary data. A thematic data analysis technique was employed. The study revealed that entrepreneurship education promotes creativity and innovation needed to eradicate poverty and unemployment in our country. Furthermore, data show, among other things, that the basic education system is faced with challenges in teacher selection, resources, and infrastructure for an array of information. It is recommended that the basic education system invests in training Technology teachers properly towards content knowledge and recruitment of teachers qualified to teach the subject.